The Role of Modern Media in Preserving African Moral Values and Promoting Economic Development in Ghana - Thomas Azagsiba Agana; Michael Pervarah; Lawrence Naaikuur (New Advances in Business, Management and Economics Vol. 3, 2025)
In the modern era of globalisation, the media have become a powerful tool that surpasses physical borders, facilitating the flow of ideas, information, and cultural manifestations around the globe. This paper delved into the effects of modern media on the preservation of traditional African moral values and economic development in Ghana. The paper is purely qualitative and relies mainly on related literature. Content and thematic analyses were employed. It was revealed that radio and television, especially in African contexts, serve as mediums for passing down cultural norms, values, and practices. The impact of modern media on moral ideals and cultural practices in sub-Saharan Africa is subject to variation depending on socio-economic conditions, rates of urbanisation, and levels of technical accessibility. By showcasing traditional music, storytelling, and other cultural elements, media platforms contribute to maintaining a sense of continuity in cultural identity. The ability to convey perceptions, hopes and dreams unrestricted on these platforms enables Africans to actively participate in shaping their cultural narrative. It was revealed that increased media consumption correlates with a rise in support for Lesbian, Gay, Bisexual, Transgender, Queer, or Questioning, Intersex, Asexual and More (LGBTQIA+) rights in Africa. Also, media can be used as a tool for exacerbating hate speech and propaganda. Media literacy programmes and public awareness campaigns can educate citizens about media’s influence and encourage critical thinking. Education systems should integrate cultural education highlighting traditional values, history, and practices into the academic curriculum. Academic institutions should invest in research to continuously monitor media’s impact on cultural values and economic development. In conclusion, the findings have shown that the media and the showcase of foreign media content have had both positive and negative effects on the economic development and preservation of Ghanaian and African traditional moral values.